2018
DOI: 10.1186/s13567-018-0584-0
|View full text |Cite
|
Sign up to set email alerts
|

Porcine sapovirus Cowden strain enters LLC-PK cells via clathrin- and cholesterol-dependent endocytosis with the requirement of dynamin II

Abstract: Caliciviruses in the genus Sapovirus are a significant cause of viral gastroenteritis in humans and animals. However, the mechanism of their entry into cells is not well characterized. Here, we determined the entry mechanism of porcine sapovirus (PSaV) strain Cowden into permissive LLC-PK cells. The inhibition of clathrin-mediated endocytosis using chlorpromazine, siRNAs, and a dominant negative (DN) mutant blocked entry and infection of PSaV Cowden strain, confirming a role for clathrin-mediated internalizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…7A ). Confirming the results of our recent report ( 33 ), these data indicated that uncoating of PSaV particles was completed at 90 mpi.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…7A ). Confirming the results of our recent report ( 33 ), these data indicated that uncoating of PSaV particles was completed at 90 mpi.…”
Section: Resultssupporting
confidence: 91%
“…The above-described results imply that PSaV-induced early activation of PI3K/Akt and MEK/ERK signaling pathways might be involved in the virus entry process. In our previous report, we demonstrated that PSaV enters cells through clathrin- and cholesterol-mediated endocytosis and travels from early to late endosomes ( 33 ). Since these membrane lipid rafts compartmentalize cellular processes by acting as a signaling platform ( 44 ), we tested whether cholesterol-perturbing drugs could affect these signaling pathways in response to PSaV infection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each VP1 monomer has 2 domains: a shell (S) domain and a protrusion (P) domain. Binding of the P domains to host receptors triggers receptor-mediated endocytosis that depends on clathrin, dynamin II, and/or cholesterol [108][109][110] as shown in Table 2, and the endocytosis is followed by penetration of the viral genome into the host cytosol for multiplication. The use of neoglycoproteins for binding studies has revealed that virus-like particles (VLPs) of Chron1 (GII.3), Dijon (GII.4), and Norwalk (GI.1) strains bind to Le b and H type 1 chain glycoconjugates.…”
Section: Caliciviridaementioning
confidence: 99%